Characteristics of binge eating disorder in relation to diagnostic criteria - Wilfley D; Citrome L; Herman B (Neuropsychiatric Disease and Treatment)
Denise E Wilfley,1 Leslie Citrome,2 Barry K Herman3 1Department of Psychiatry, Washington University School of Medicine, St Louis, MO, 2Department of Psychiatry & Behavioral Sciences, New York Medical College, Valhalla, NY, 3Global Medical Affairs, Shire, Lexington, MA, USA Abstract: The objective of this review was to examine the evidentiary basis for binge eating disorder (BED) with reference to the Diagnostic and Statistical Manual of Mental Disorders – Fifth Edition (DSM-5) diagnostic criteria for BED. A PubMed search restricted to titles and abstracts of English-language reviews, meta-analyses, clinical trials, randomized controlled trials, journal articles, and letters using human participants was conducted on August 7, 2015, using keywords that included “binge eating disorder,” DSM-5, DSM-IV, guilt, shame, embarrassment, quantity, psychological, behavior, and “shape and weight concerns.” Of the 257 retrieved publications, 60 publications were considered relevant to discussions related to DSM-5 diagnostic criteria and were included in the current review, and 20 additional references were also included on the basis of the authors’ knowledge and/or on a review of the reference lists from relevant articles obtained through the literature search. Evidence supports the duration/frequency criterion for BED and the primary importance of loss of control and marked distress in identifying individuals with BED. Although overvaluation of shape/weight is not a diagnostic criterion, its relationship to the severity of BED psychopathology may identify a unique subset of individuals with BED. Additionally, individuals with BED often exhibit a clinical profile consisting of psychiatric (eg, mood, obsessive–compulsive, and impulsive disorders) and medical (eg, gastrointestinal symptoms, metabolic syndrome, and type 2 diabetes) comorbidities and behavioral profiles (eg, overconsumption of calories outside of a binge eating episode and emotional eating). Future revisions of the BED diagnostic criteria should consider the inclusion of BED subtypes, perhaps based on the overvaluation of shape/weight, and an evidence-based reassessment of severity criteria. Keywords: binge eating disorder, diagnosis, obesity, psychotherapy, pharmacotherapy, psychopathology